2007
DOI: 10.1177/0883073807306272
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Spasms as an Epileptic Feature of DEND Syndrome Associated With an Activating Mutation in the Potassium Adenosine Triphosphate (ATP) Channel, Kir6.2

Abstract: Activating mutations in the Kir6.2 subunit of the adenosine triphosphate-sensitive potassium (KATP) channel is a cause of neonatal diabetes associated with various neurological disorders that include developmental delay, epilepsy, and neonatal diabetes (known together as DEND syndrome). This article reports a girl who developed infantile spasms and early onset diabetes mellitus at the age of 3 months and revealed DEND syndrome with a heterozygous activating mutation in Kir6.2. Infantile spasms with hypsarrhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…There is marked cerebellar atrophy and infantile spasms [42,43]. IS can also be associated in DEND syndrome, characterized by developmental delay, epilepsy and neonatal diabetes [44]. …”
Section: Etiologymentioning
confidence: 99%
“…There is marked cerebellar atrophy and infantile spasms [42,43]. IS can also be associated in DEND syndrome, characterized by developmental delay, epilepsy and neonatal diabetes [44]. …”
Section: Etiologymentioning
confidence: 99%
“…The fi rst patient described with a mutation at codon 166 with substitution of cysteine by phenylalanine (C166F) presented with neonatal diabetes, full DEND syndrome and dysmorphic features including prominent metopic suture, bilateral ptosis and down turned mouth, but she died from aspiration pneumonia at the age of 6 months after partial and transitory control of epilepsy with tolbutamide (0.75 mg/kg/d) combined with ACTH therapy (26,27). Afterwards, Flanagan et al (19) demonstrated the C166Y mutation (substitution of cysteine by tyrosine) in our patient, followed by another case (C166Y) described by Suzuki et al (28) of neonatal diabetes with DEND syndrome, dysmorphic facial features and arthrogryposis who has been treated exclusively with insulin.…”
Section: Kcnj11 Mutation and Glibenclamide Insensitivitymentioning
confidence: 99%
“…It has been reported that neuronal K ATP channels show an ability to adjust cell excitability [11][12][13] . Pharmacological and genetic studies have provided evidence to further support the roles of neuronal K ATP channels in the control of neuronal excitability and seizure propagation by depolarizing presynaptic neuron and subsequently by inhibiting the release of excitatory neurotransmitter, or by regulating GABA transporters [1,[14][15][16][17][18][19] . However, little is known about the roles of astrocytic sK ATP /mitoK ATP channels in epileptogenesis.…”
Section: Astrocytic K Atp Channels and Astrocytic Gjs In Epileptogenesismentioning
confidence: 99%
“…Manipulation of the K ATP channel status in various cellular types and at various intracellular locations has shown a variety of functional roles [3,[7][8][9][10] . It has been revealed that neuronal K ATP channels in the brain are involved in the control of neuronal excitability [11][12][13] and seizure propagation [1,[14][15][16][17][18][19] . The roles that glial K ATP channels play are receiving renewed attention due to improved understanding of the molecular events underpinning the physiological functions of glial cells.…”
Section: Introductionmentioning
confidence: 99%